1971
DOI: 10.1079/bjn19710006
|View full text |Cite
|
Sign up to set email alerts
|

The expected and observed changes in the intake of three hays by sheep after shearing

Abstract: I . The effect of shearing Merino wethers on their voluntary intake of three hays of different digestibilities was studied in two experiments.2. In Expt I , six groups of ten wethers in metabolism crates were given lucerne (a goodquality) hay, setaria (a medium-quality) hay and pangola (a poor-quality) hay ad Zib., at an average room temperature of 25'. The sheep of one of the two groups given each hay were shorn at the beginning of the experimental period. For 4 weeks after shearing, the shorn sheep given luc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

1974
1974
1992
1992

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Although empty-body weight tended to decrease with exercise in the present study (Table 2) this decrease was not statistically significant. However, the duration of increased energy demand was much shorter in this case than in the experiment of Minson & Ternouth (1971).…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…Although empty-body weight tended to decrease with exercise in the present study (Table 2) this decrease was not statistically significant. However, the duration of increased energy demand was much shorter in this case than in the experiment of Minson & Ternouth (1971).…”
Section: Discussioncontrasting
confidence: 49%
“…The work of Graham, Nicol & Christopherson (1982) suggests that these increases are also obtained through increased rumen tissue weight and a concomitant increase in rumen fill. Body weight losses in the study by Minson & Ternouth (1971) indicated a negative balance between energy demand and energy supply. Although empty-body weight tended to decrease with exercise in the present study (Table 2) this decrease was not statistically significant.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…The depression persisted for at least three weeks in the WL group, while the WG group increased their intake. The data of both Weston (1970) and Minson and Ternouth (1971) also indicate a post-shearing depression of intake in conditions which were cooler than the tilermoneutral conditions specified by Graham et al (1959) for newly shorn sheep with similar food intakes. This depression is increased and extended for a longer time under ambient temperatures between -3 and 8oc (Lynch unpublished).…”
Section: Statistical Analysesmentioning
confidence: 75%